Hybrid Arc: Combining Forward IMRT and Double arc VMAT in Locally Advanced Rectum Cancer - Saglam, Yucel; Bolukbasi, Yasemin; Alpan, Vildan; Sezen, Duygu; Bingolbali, Ayhan; Selek, Ugur (AKAD DOKTORLAR YAYINEVI, 2019)
To investigate the potential of increasing target dose conformity and organ at risk (OAR) sparing of Hybrid Arc approach for patients with locally advanced rectum cancer (LARC) in comparison to VMAT and inverse IMRT. This study consisted of thirteen patients who had LARC, were treated with VMAT in 25Gy in 5 fractions. Two different new plans for each patient were generated on Pinnacle TPS by inverse IMRT (7 fields) and Hybrid Arc technique (combining forward IMRT (3 fields) with 20% weight and VMAT (double full arcs) with 80% weight). Treatment plans; Hybrid Arc, VMAT and inverse IMRT, were assessed using dose-volume histogram (DVH) parameters of OARs doses for bladder, small bowel, femur heads and penile bulb in male patients' cases. Ad-ditionally, monitor units (MU), conformity index (CI) and homogeneity index (HI) for clinical target volumes (CTV) were compared for all three techniques. Most DVH parameters pertaining to OARs significantly favored Hybrid Arc technique compared to VMAT and inverse IMRT. Hybrid Arc provided significantly improved Bladder DVH parameters in comparison to IMRT & VMAT. The Hybrid technique provided significantly lower small bowel doses in comparison to inverse IMRT and VMAT for all DVH pa-rameters. Mean MU of inverse IMRT was the highest one (MUIMRT= 1803, p= 0.001 vs VMAT; p= 0.023 vs Hybrid Arc). The target dose conformity and homogeneity of VMAT were better than the other two techniques. Hybrid technique combined the advantages of forward IMRT and VMAT for better OAR sparing in comparison to VMAT and inverse IMRT.
Keywords: Rectal cancer; IMRT; VMAT; Hybrid; VOLUMETRIC-MODULATED ARC; SIMULTANEOUS INTEGRATED BOOST; SMALL-BOWEL TOXICITY; CELL LUNG-CANCER; RADIATION-THERAPY; RADIOTHERAPY; IRRADIATION; CHEMORADIOTHERAPY; DOSIMETRY; Oncology